Social Norms and Conditional Cooperative Taxpayers - Christian Traxler (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2006)
This paper incorporates tax morale into the Allingham Sandmo (1972) model of income tax evasion. Tax morale is interpreted as a social norm for tax compliance. The norm strength, depending on the share of evaders in the society, is endogenously derived. Taxpayers act conditionally cooperative, as their evasion decision depends on the other agents' compliance. We characterize an equilibrium which accounts for this interdependence and study the impact of tax and deterrence policies on compliance. Our analysis is then extended to the case of a society which consists of heterogenous communities where individual evasion decisions are embedded in a complex social structure. In this scenario, behavior is crucially influenced by the norm compliance among morale reference groups. Within this framework, we discuss the role of belief management and belief leadership as alternative policy tools.
urn:nbn:de:bvb:19-epub-1202-9
Keywords: H26; Z13; K42; 330; Tax Evasion; Tax Morale; Social Norms; Conditional Cooperation; Soziale Norm; Steuermoral; Steuertheorie; Theorie